TRANSFER PENGETAHUAN TEKNOLOGI POMPA HIDRAM (NON LISTRIK & BBM) DI DESA LALOUESAMBA KABUPATEN KONAWE SELATAN - Agustan Agustan; Edward Ngii; Adris Ade Putra; Sitti Nurjannah Ahmad; Rudi Balaka; Fitriah S Fitriah S (Jurnal Pengabdian NUSANTARA, 2022)
Lalouesamba Village is one of the youngest villages in the South Konawe Regency, with a non-coastal slope topography of 82 meters above sea level and an area of about 4.1 km2. The majority are farming/gardening, coolies, and construction workers are the main occupations. Potential water resources include rivers with a width of 3-5 meters around the village. Each 1 artesian spot, boiling water spot, murky water borehole, and 5 units of wells with a depth of 15 meters. The problem with this village partner is that there is still a lack of access to clean water, so the solution offered to lift/pump the potential for river flow is to use a hydraulic ram pump without electricity & fuel. Therefore, this community service activity aims to provide an understanding of hydraulic ram pump knowledge and open insight into the potential for welfare due to the pump. The results of the transfer of knowledge of hydraulic ram pumps show a good indication with the achievement of the main material up to 80% based on the results of the feedback questionnaire and it can be stated that the villagers of Lalouesamba are ready to advance to the next stage, namely practical training on assembling/making hydraulic ram pumps. Requests for additional discussion from residents and village heads are evidence of the enthusiastic response, which is a sign of the opening of insight into the potential of hydram pumps for the welfare of villagers after receiving enlightenment about hydram knowledge